2021
DOI: 10.3390/ijms22115936
|View full text |Cite
|
Sign up to set email alerts
|

A Screening of the MMV Pandemic Response Box Reveals Epetraborole as A New Potent Inhibitor against Mycobacterium abscessus

Abstract: Mycobacterium abscessus is the one of the most feared bacterial respiratory pathogens in the world. Unfortunately, there are many problems with the current M. abscessus therapies available. These problems include misdiagnoses, high drug resistance, poor long-term treatment outcomes, and high costs. Until now, there have only been a few new compounds or drug formulations which are active against M. abscessus, and these are present in preclinical and clinical development only. With that in mind, new and more pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 46 publications
(57 reference statements)
3
13
0
Order By: Relevance
“…Our data and two recent publications [43,44] confirmed the activity of benzoxaboroles against mycobacteria using zebrafish and murine models of infection and we showed that benzoxaboroles can be potentiated when combined with norvaline. Specifically, we demonstrated that the combination of EPT with norvaline reduces the emergence of M. abscessus and M. tuberculosis mutants and results in increased activity in vivo compared to EPT.…”
Section: Discussionsupporting
confidence: 86%
“…Our data and two recent publications [43,44] confirmed the activity of benzoxaboroles against mycobacteria using zebrafish and murine models of infection and we showed that benzoxaboroles can be potentiated when combined with norvaline. Specifically, we demonstrated that the combination of EPT with norvaline reduces the emergence of M. abscessus and M. tuberculosis mutants and results in increased activity in vivo compared to EPT.…”
Section: Discussionsupporting
confidence: 86%
“…In conclusion, we show that epetraborole, an advanced nonhalogenated 3-aminomethyl benzoxaborole developed for Gram-negative infections, is also active against M. abscessus in vitro and in a mouse model of infection. This agrees with a recent publication that identified epetraborole in a screen of the MMV pandemic response box for anti- M. abscessus activity and reported this compound’s efficacy against M. abscessus in a zebrafish infection model ( 19 ). Our findings reaffirm leucyl-tRNA synthetase as an attractive target against M. abscessus and expand the repertoire of advanced lead compounds for the discovery of a benzoxaborole-based candidate for the treatment of M. abscessus lung disease.…”
Section: Introductionsupporting
confidence: 92%
“…The box corresponds to a collection of 400 structurally diverse compounds for screening against infectious diseases and other neglected maladies. Within this compound collection, inhibitors of the replication of SARS Cov 2 ( 14 ) and Zika virus ( 15 ), in addition to anti-amoebic drugs ( 16 ), antimalarials ( 17 ), antischistosomals ( 18 ), and inhibitors of Mycobacterium abscessus ( 19 ) have been described. In this study, we screened the Pandemic Response Box collection for activity against three fungal pathogens with high lethality and exceedingly ineffective treatment options: Cryptococcus neoformans , Cryptococcus deuterogattii , and C. auris .…”
Section: Introductionmentioning
confidence: 99%